Assessment of Wood Quality of Grevillea robusta from Bangalore,karnataka - Kamala, B. S.; Kothiyal, Vimal; Sharma, S. K. (Indian Forester, 2000)
Physical and mechanical properties of Grevillea robusta procured from Institute of Wood Science and Technology campus, Bangalore were evaluated. Hardness and nail holding power are maximum in basal portion. Variation are found significant with height for sp.gr.,FS at LP and MCS in green condition. Based on the strength properties, the timber is classified as moderately heavy, moderately strong, not tough, moderately steady and soft. The timber is classified as group III constructional timber. It may be used for door shutters and frames, joinery, furniture, decorative veneers, turnery and packing cases.